Attention to menstrual hygiene management in schools: An analysis of education policy documents in low- and middle-income countries. (November 2017) - Sommer, Marni; Figueroa, Chantal; Kwauk, Christina; Jones, Meredith; Fyles, Nora
Highlights: Education sector plans lack explicit mention of menstrual hygiene management (MHM). Gender and education policies also have limited mention of menstruation terms. Girls' education strategies are more likely to address MHM. The absence of MHM terms is a symptom of larger gender discrimination in schools. WASH in Schools guidelines illustrate how the education sector can address MHM. Abstract: Recent decades have seen a push for gender parity in education in low resource countries. Attention is shifting to how school environments hinder the achievement of gender equality. One effort, primarily led by the water, sanitation and hygiene sector, includes a focus on the needs of menstruating girls. This policy review aims to understand how the education sector is addressing menstruation management. We conducted an analysis of select education policy documents in 21 countries, including a frequency count and narrative analysis of relevant keywords. Findings suggest that existing national education policies inadequately provide for sufficient water and sanitation facilities or other menstruation-related improvements needed in schools. More recently developed WASH in schools policies present examples of potential approaches for education stakeholders to better address girls' menstrual needs in school through policy and program responses.